Carboxylic acids of marine evaporitic oils from Sergipe-Alagoas Basin, Brazil - Rodrigues, D. C.; Koike, L.; Reis, FDM; Alves, H. P.; Chang, H. K.; Trindade, L. A.; Marsaioli, A. J. (Elsevier B.V., 2000)
A. suite of 10 different marine evaporitic oil samples from Sergipe-Alagoas Basin, Brazil was studied for its biomarker content, in particular its acidic constituents. The oils showed different molecular distributions and relative abundances of n-alkanoic, isoprenoid and hopanoic acids. The observed differences were assigned to the incorporation of immature organic matter in the oils and fractionation along the migration pathway. The diagenetic precursor functionality (alcohol/ether or acid) was proposed based on the comparison of the relative abundances of the neutral and acidic biomarkers (hopanoids, isoprenoids, alkyl-steranes, monoaromatic alkyl-steroids). In the acidic fraction, 3 series of steroid-alkanoic acids and monoaromatic steroid-alkanoic acids (steroid-methanoic, ethanoic and propanoic acids and monoaromatic steroid-methanoic, ethanoic and propanoic acids) were detected, while in the neutral fraction only 2 series of each corresponding class could be observed (methyl and ethyl-steranes and monoaromatic methyl and ethyl-steroids). These carbon shifts suggest that decarboxylation is an important process in the formation of the alkyrsteranes and monoaromatic alkyl-steroids, and we infer that carboxylic acids are the diagenetic precursors of these classes of compounds. When alcohol or ether are the diagenetic precursors (isoprenoids and hopanoids), no significant differences in the molecular distributions between neutral and acidic fractions were observed. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: Sergipe-Alagoas Basin; Brazil; Carmopolis oil field; marine evaporitic petroleum; acidic biomakers; steroid-alkanoic acids; C-25 regular isoprenoid acid